Design, synthesis and biological evaluation of tryptamine salicylic acid derivatives as potential antitumor agents. Issue 4 (18th January 2019) - Xiong, Runde; He, Dongxiu; Deng, Xiangping; Liu, Juan; Lei, Xiaoyong; Xie, Zhizhong; Cao, Xuan; Chen, Yanming; Peng, Junmei; Tang, Guotao
Abstract : According to the combination principle, target compounds were designed, and compoundE20 might be a promising anti-tumor agent targeting gastric cancer. Abstract : A series of tryptamine salicylic acid derivatives were synthesized and their antiproliferative activity against MGC-803, MCF-7, HepG2, A549 and HeLa cell lines was evaluated. The structure–activity relationship (SAR) study revealed that different substitutions of the C5 and C3′–C5′ positions have certain effects on the anti-proliferation activity. The growth assay revealed that N -[2-(5-bromo-1 H -indol-3-yl)-ethyl]-2-hydroxy-3-methyl-benzamide (E20 ) showed the most potent and broad-spectrum anticancer inhibition of all the cell lines evaluated, and was only more potent than 5-Fu for the gastric cancer cell line. Preliminary studies indicated that compoundE20 could inhibit colony formation and migration of MGC-803 cells. The flow cytometry (FCM) results showed that compoundE20 arrested the cell cycle in the G2/M phase and induced apoptosis of MGC-803 cells in a concentration-dependent manner. In addition, the western blot results showed thatE20 can down-regulate the expression of hexokinase 2. Our studies suggest that the framework of N -[2-(5-bromo-1 H -indol-3-yl)-ethyl]-2-hydroxy-3-methyl-benzamide may be consider as a new type of chemical for designing effective anti-cancer drugs targeting gastric cancer cells.